On Creative Self-Driving Cars: Hire the Computational Logicians, Fast. Issue 8 (13th September 2016) - Bringsjord, Selmer; Sen, Atriya
ABSTRACT: There can be no denying that it is entirely possible for a car-manufacturing company like Daimler to build and the deploy self-driving cars without hiring a single computational logician. However, for reasons we explain herein, a logician-less approach to engineering self-driving automobiles (and, for that matter, self-moving vehicles of any consequence, in general) is a profoundly unwise one. As we shall see, the folly of leaving aside logic has absolutely nothing to do with the standard and stale red-herring concern that self-driving cars will face exotic human-style ethical dilemmas the philosophers have a passionate penchant for.